2016
DOI: 10.11604/pamj.2016.25.57.8880
|View full text |Cite
|
Sign up to set email alerts
|

Le recours systématique à l’estimation échographique du poids fœtal en salle de naissances augmente-t-il le risque d’accouchement par césarienne?

Abstract: L’échographie est un précieux outil utilisé quotidiennement en salle de travail. Ses applications sont multiples. L’objectif est d’évaluer si le recours systématique à une estimation échographique du poids fœtal et en salle de naissances augmente le risque d’accouchement par césarienne. Etude de cohorte monocentrique. Nous avons inclus toutes les parturientes avec des grossesses monofœtales qui avaient accouché à un terme ≥ 39 SA. Nous avons exclu toutes les patientes avec une contre indication à l'accouchemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Plonka et al [31] showed that fetuses with different conditions should be assessed with different formulas. Dimassi et al [32] showed that ultrasound examination in the delivery room was reasonable, but the accuracy rate of EFW was only 62.1%. The model established in this study did not include fetal head measurement variables, which avoided the influence of standard measurement section acquisition factors.…”
Section: Discussionmentioning
confidence: 99%
“…Plonka et al [31] showed that fetuses with different conditions should be assessed with different formulas. Dimassi et al [32] showed that ultrasound examination in the delivery room was reasonable, but the accuracy rate of EFW was only 62.1%. The model established in this study did not include fetal head measurement variables, which avoided the influence of standard measurement section acquisition factors.…”
Section: Discussionmentioning
confidence: 99%